Factores Asociados a la Dislipidemia y Diabetes Mellitus tipo II en Pacientes de 40-60 años, en el Hospital Santa Margarita de EsSalud de Andahuaylas 2015-2016. - Palomino Mallqui, Juana Nancy (2020)
The purpose of the study was to determine the relationship between the factors associated with dyslipidemia and diabetes Mellitus II in patients between 40 and 60 years of age, from the Santa Margarita Hospital, EsSalud of Andahuaylas. The universe consists of 1901 patients from 40 to 60 years of age in 2015 and 2125 patients in 2016, the design used to determine the risk factors is the case and control with 448 patients with dyslipidemia. The study is of a retrospective nature, where an analytical study of registered data of the patients of the years 2015 and 2016 was carried out, to evaluate the levels of cholesterol, triglycerides, HDL, and LDL, as well as the associated factors; sedentary lifestyle, smoking, body mass index in relation to age and glucose. To find the relationship of the variables, the Pearson Chi square statistic was used. Arriving at the following results: a. There is a direct relationship between the factors associated with dyslipidemia and type II diabetes mellitus in patients aged 40 to 60 years at the Hospital of Andahuaylas in the years 2015-2016.